Evidence-Based Comparison of Robotic and Open Radical Prostatectomy - William T. Lowrance; Tatum V. Tarin; Shahrokh F. Shariat (The Scientific World Journal)
The rapid adoption of robotic-assisted laparoscopic radical prostatectomy (RALP) has occurred despite a lack of high-quality evidence demonstrating its oncologic advantages, safety, or cost effectiveness compared with open radical retropubic prostatectomy (ORP). This review examines the current literature comparing ORP and RALP, focusing on perioperative, oncologic, functional, and economic outcomes.